FENOMENA NOMINEE ASING DI BALI: TINJAUAN HUKUM DAN KEDAULATAN NEGARA - Arianti, Wayan Nanda Yuri; Sohirin; Utami, Devina Yuka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The phenomenon of foreign nominees in Bali has increased significantly in line with the rising interest of foreign nationals in investing in the tourism and property sectors. This study aims to analyze the practice of foreign nominees in business investments in Bali, examine its implications for state sovereignty, and assess the effectiveness of the existing legal framework. This research employs a normative juridical method with statutory and conceptual approaches, utilizing secondary data derived from legislation, court decisions, and relevant scholarly literature. The findings reveal that foreign nominee practices are conducted through private agreements that designate Indonesian citizens (WNI) as formal owners while the actual control remains with foreign nationals (WNA). Such practices violate the Basic Agrarian Law and the Investment Law, posing threats to legal and economic sovereignty. Legal loopholes exploited by foreign investors are exacerbated by weak supervision and inconsistent law enforcement. Therefore, strengthening legal regulations, enforcing beneficial ownership transparency, and enhancing inter-agency coordination are crucial measures to prevent nominee practices that undermine state sovereignty.